Investigation of the Fundamental Plane Relationship For the Evolution of the Elliptical and Lenticular Galaxies - Khalid Mohammed (College of Education for Pure Sciences, 2024)
The Fundamental Plane relates the effective radius and surface brightness of an early-type galaxy to its velocity dispersion. It is important in understanding galaxy formation and evolution processes. The present work aims to investigate this relation as well as Faber-Jackson and Kormendy relations for both elliptical and lenticular galaxies separately in order to compare them. For this purpose, we take a sample of 140 early-type galaxies (70 elliptical galaxies and 70 lenticular ones), extracted from the extensive catalogue of early-type galaxies, and investigate them by using data analysis and visualization software. This work confirms that elliptical and lenticular galaxies are located almost in the same fundamental plane, with an rms scatter of 0.140 for ellipticals and 0.172 for lenticulars. Yet, elliptical galaxies show a tighter relationship than lenticular galaxies. This implies that elliptical galaxies obey the Fundamental Plane relation better than lenticular galaxies. Also, the two morphological types of galaxies obey Faber-Jackson relation, with an rms scatter of 0.101 for ellipticals and 0.873 for lenticulars. They, also, obey Kormendy relation, with an rms scatter of 0.600 for elliptical and 0.685 for lenticulars. These results indicate that the two relations are, also, more obvious in the case of elliptical galaxies.